A New Putative Hybrid in Conomurex Fischer, 1884 (Mollusca, Neostromboidae, Strombidae) With Notes on the Types of Hybrids - Maxwell, Stephen J. (European Journal of Applied Sciences, 2022)
The propensity for hybridisation is well established in Strombidae. I propose that there are three forms of hybridisation: first the true hybrids; second reticulatory hybrids; and third diversificatory hybrids. The new putative true hybrid between Conomurex decorus and Conomurex luhuanus is known from a single example form central Indonesia and represents the first example of intrageneric hybridization for Conomurex. Furthermore, this paper introduces and illustrates the novel concept of diktyzonos for regions or reticulation within and between taxa, and how hybrids can be identified after assessing the dikyzonotic region.